2004
DOI: 10.1007/s00134-004-2422-2
|View full text |Cite
|
Sign up to set email alerts
|

Research issues in the evaluation of cognitive impairment in intensive care unit survivors

Abstract: Neuropsychological assessment has been utilized extensively in the research of cognitive outcomes associated with medical illnesses, such as HIV, and post-surgical procedures, such as coronary artery bypass graft. However, few investigations of intensive care unit (ICU) survivors have examined cognitive function as a clinical outcome. Significant clinical questions exist regarding the impact of critical illness on long-term cognitive function. Many of these questions can be systematically evaluated through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 57 publications
1
30
0
1
Order By: Relevance
“…Previous reports involving intensive care unit survivors demonstrated cognitive impairment at discharge from the hospital (9)(10)(11)(12)(13)(14)(15)(16)(17). In long-term follow-up studies most patients showed improvement in overall cognitive function; however, some cognitive skills, such as memory, were not completely recovered (9,13,14).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous reports involving intensive care unit survivors demonstrated cognitive impairment at discharge from the hospital (9)(10)(11)(12)(13)(14)(15)(16)(17). In long-term follow-up studies most patients showed improvement in overall cognitive function; however, some cognitive skills, such as memory, were not completely recovered (9,13,14).…”
Section: Discussionmentioning
confidence: 89%
“…Recently, several studies have demonstrated that critical care survivors present long-term cognitive impairment, including alterations in memory, attention, concentration, and/or global loss of cognitive function (9)(10)(11)(12)(13)(14)(15)(16)(17). However, the neurobiological mechanisms involved in this cognitive impairment remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…13 Likewise, survivors from critical care, including septic patients, have well-documented persistent neurocognitive deficits and develop psychiatric disorders. [14][15][16][17][18][19][20][21][22][23] The interaction between sepsis and the brain is an opportunity to study how systemic inflammation affects brain function. Most studies about the mechanisms of SE have used animals or cell cultures, and improved our understanding of how the CNS is affected by endotoxins and cytokines, but whether this is related to clinical SE remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…31 To date, there is still a lack of consensus on how to define LTCI-CI especially in comparison to other forms of cognitive impairments, though broad agreement exists that a uniform definition would be helpful. 60 Patients have been tested 25 with neuropsychological batteries, which assess different cognitive domains: mental status, psychomotor speed, verbal fluency, working memory, verbal memory, visual memory and visuo-construction. Though definitions vary, they have tended to be quite restrictive (e.g., difficult to reach), as using such definitions ensure that subjects defined as 'impaired' are truly impaired and not false positives.…”
Section: Long-term Cognitive Impairment After a Critical Illnessmentioning
confidence: 99%